Design of broadband circularly polarised printed monopole antennas for indoor wireless communication systems - Alsariera, Hussein Salameh Mahmoud (2021)
With the rapid changes in wireless communication systems, indoor wireless communication (IWC) technology has undergone tremendous development. Antennas are crucial components of IWC systems that transmit and receive signals within indoor environments. Thus, the development of indoor technology is highly dependent on the development of indoor antennas. However, indoor environments with a limited space require the fewest number of indoor antenna units and the smallest indoor antenna size. Hence, indoor antennas with a compact size and broad applications have become widely preferred. In an IWC tem, the use of circularly polarised (CP) antennas is generally important, especially in dense indoor environments, because relative to linearly polarised (LP) antennas, CP antennas reduce polarisation mismatch and multipath losses. Conventional broadband CP antennas have been used for IWC systems. However, these antennas are bulky in size and feature a heavy profile. They are also expensive and difficult o design and fabricate. Thus, broadband CP printed monopole antennas (BCPPMAS) have received considerable attention in the field of wircless communication because of their compact size, low profile, low cost, simple structure and capability of providing broad impedance bandwidth (IBW) and axial ratio bandwidth (ARBW). However, these antennas have a difficulties in the trade-off between the antenna's bands (TBW and ARBW) with high overlapping percentage and their structure size which restricts their use in IWC sy Therefore, this thesis aimed to design a new structure for BCPPMAs which ew functionality for indoor antennas. Two design topology approaches for BCPPMAs were introduced: the biplanar topology approach based on the microstrip feeding technique and the uniplanar topology approach based on coplanar waveguide feeding (CPW-fed) using low-cost FR4 materials. All presented antennas provided bidirectional radiation patterns with different CP senses and good gain with small variations over the majority of the achieved CP band. The main proposed CP antenna_designs, namely, the P-shaped, L-shaped and modified rectangular-shaped BCPPMAS were simulated, fabricated and measured. The antennas provided broad IBW and ARBW greater than 100%, Moreover, the bandwidths showed a wide overlapping ratio between them of more than 89%. while the measured IBW and ARBW of the proposed modified rectangular CPW-fed BCPPMA are 108.5% (1.825-6.15 GHz) and 107.7% (1.8~ 6 Giz), respectively. This design retains a compact size of 35 mm x 35 mm and a wide overlapping percentage of 97%. The measurement results showed a good agreement with the simulation results. The benefits of the proposed antennas include broad IBW and ARBW, compact size and simple design. Hence, they are suitable candidates for IWC systems. The results of this work can facilitate improvements in broadband wireless communication systems and afford them with good tuning capabilites